Pengaruh Faktor Lingkungan Pada Penentuan Materi Kesalahan Dalam Audit Laporan - Ahmad Jarot; Cris Kuntadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose in this study was to determine the effect of environmental factors on the determination of error material in the audit of financial statements. Ind facto environment is accountability, independent auditors, experience, auditory performance and auditory professionalism in determining the quality of the audit. The approach used is Quantitative by using multiple linear regression analysis. The results showed that Value from R Square in the study was 0.616 (61.6%) meaning that there were still 38.4% of factors (variable) that could affect the quality of the audit. For this reason, researchers can further add to the use of other variables other than the four variables that have been used in this study, such as leadership styles, auditor competence competencies, and time pressure budget.